Second language prosody and its development: connection between different aspects. Issue 6 (1st November 2020) - Kuronen, Mikko; Tergujeff, Elina
ABSTRACT: This study focuses on the development of L2 prosody and, in particular, whether different aspects can affect each other. Finnish-speaking learners of Swedish took part in a pronunciation and oral skills course and were recorded for various speaking tasks before and after the experimental intervention. Read-aloud declarative sentences (statements) from nine learners were acoustically analysed for several tonal and temporal aspects, focusing on the marking of primary stress. The results reveal that the learning of Swedish tonal word accent 2 (H*LH) facilitates other tonal developments towards native-like utterance intonation. A link between tonal and temporal developments in the marking of primary stress was, however, not found, but the duration measurements suggest that articulation rate and tonal developments may be connected. The study's implications for teaching and future research regarding any L2 – not only Swedish – include that aspects of learning L2 prosody should not be treated as separate, and that more emphasis should be placed on the possible connections between the learning of different aspects.